Evaluation on effects of using low biodiesel blends in a EURO 5 passenger vehicle equipped with a common-rail diesel engine. (15th May 2015) - Serrano, L.; Lopes, M.; Pires, N.; Ribeiro, I.; Cascão, P.; Tarelho, L.; Monteiro, A.; Nielsen, O.; da Silva, M. Gameiro; Borrego, C.
Highlights: An EURO 5 passenger vehicle was tested under NEDC (New European Driving Cycle) and full load condition, using B0, B7 and B20. The fuel consumption, NOx emissions and performance were analyzed. Fuel consumption is not proportionally affected by LHV of the fuel. Biodiesel use doesn't decrease the capabilities of the engine. The higher power was reached with B7. Abstract: The effects of the use of low biodiesel blends in performance, fuel consumption and NOx emissions was investigated during tests carried out with a Renault Megane 1.5 dCi equipped with recent injection and exhaust emission control technologies. To accomplish this goal, several tests were performed using the European homologation cycle concerning CO2 emissions of vehicles, known as the New European Driving Cycle (NEDC). This was executed using a chassis dynamometer, a fuel weighting equipment, an exhaust emissions analyzer and the software developed to acquire data and control the execution of the cycle. Besides the accomplishment of the NEDC cycle tests with three diverse fuel blends, performance tests were also realized, enabling to get the full load engine response considering the use of different fuels. The chosen biodiesel produced from original oils of soybean (84%) and palm (16%), was mixed in proportions of 0%, 7%, and 20% on a volumetric basis, allowing to test comparatively the results for these different fuel blends (B0, B7 and B20). The obtained results reveal some interesting findings regarding all the involved aspects. The consumption was not consistently increased with the use of biodiesel, revealing the existence of other factors besides the lower heating value to explain the fuel consumption differences. Likewise, the NOx emissions with biodiesel use does not present significant raise. In fact, when B20 was used, the levels of NOx emitted by the vehicle present a reduction in all the NEDC, which was more pronounced in the urban part of the NEDC. The performance analysis did not reveal any relevant differences, however the use of B7 promote an improvement on torque and power in the order of 2% relatively to B0.